Analisis Kinerja dan Tarif Angkutan Umum Bus Jurusan Surakarta-Yogyakarta: Studi Kasus pada Bus Langsung Jaya, Jaya Putra dan Sri Mulyo - Suwardi Suwardi (Universitas Muhammadiyah Yogyakarta, 2009)
One of the supporting factors to improve connection between Surakarta and Yogyakarta, is the adequacy of public transportation. With the existence of adequate public transportation that meet the standard, especially Yogyakarta – Surakarta buses, activities in the two cities can be expected to increase. The activities can be economic, politic, social, safety, scientific or the others. The existing public transportation between Surakarta – Yogyakarta, needs to be evaluated because public might not satisfy the standard. The objective of the research is to analyse the operational cost and tariff of public buses serving Yogyakarta – Surakarta line. The method of this research is descriptive analysis. In this research, public work on transportation in this region was analyzed in order to improve its condition in the future. Primary data include the number of passenger, travel time, departure and arrival time. Secondary data obtained from the bus companies consist of direct and indirect operational costs, as well as fixed and variable cost. The results show that the passenger tariff after yield analysis with headway 4 minutes and the average load factor of 55.83% is IDR 8,720. At headway of 4 minutes and passenger tariff of IDR 8,000 bus companies are still suffering from loss. If the headway changed to 6 minutes , the load factor became 83.75% and the passenger tariff of IDR 5,800. It is lower than the current passenger tariff of IDR 8,000. The changing of headway from 4 minutes to 6 minutes may increase bus company profit by 27%.